2014
DOI: 10.1007/s10554-014-0510-0
|View full text |Cite
|
Sign up to set email alerts
|

Prosthesis-patient mismatch after transcatheter aortic valve implantation: impact of 2D-transthoracic echocardiography versus 3D-transesophageal echocardiography

Abstract: To investigate the role of 2D-transthoracic echocardiography (2D-TTE) and 3D-transesophageal echocardiography (3D-TEE) in the determination of aortic annulus size prior transcatheter aortic valve implantation (TAVI) and its' impact on the prevalence of patient prosthesis mismatch (PPM). Echocardiography plays an important role in measuring aortic annulus dimension in patients undergoing TAVI. This has great importance since it determines both eligibility for TAVI and selection of prosthesis type and size, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…In our study, we found that MCV had lower incidence of overall and moderate PPM than ESV. Consistently, the pooled results showed that MCV 9 , 12 14 , 17 , 18 , 22 , 31 , 33 , 37 had lower mean trans-vavular mean gradient than ESV 9 – 11 , 14 , 16 , 19 21 , 23 , 25 , 32 (MCV, 9.3 mmHg vs ESV, 10.2 mmHg, P < 0.001). Additionally, the randomized CHOICE trial 43 also revealed that MCV was associated with lower trans-valvular mean gradient than ESV (MCV vs ESV, 8 mmHg vs 9 mmHg, p = 0.004), albeit no reported data on the comparison of PPM.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In our study, we found that MCV had lower incidence of overall and moderate PPM than ESV. Consistently, the pooled results showed that MCV 9 , 12 14 , 17 , 18 , 22 , 31 , 33 , 37 had lower mean trans-vavular mean gradient than ESV 9 – 11 , 14 , 16 , 19 21 , 23 , 25 , 32 (MCV, 9.3 mmHg vs ESV, 10.2 mmHg, P < 0.001). Additionally, the randomized CHOICE trial 43 also revealed that MCV was associated with lower trans-valvular mean gradient than ESV (MCV vs ESV, 8 mmHg vs 9 mmHg, p = 0.004), albeit no reported data on the comparison of PPM.…”
Section: Discussionsupporting
confidence: 58%
“…There were 35 studies left after screening the titles and abstracts. After removing overlapping data, a total of 30 studies 9 – 37 incorporating 4,691 patients were eligible. There was 1 study 11 reporting two clusters of patients including randomized and non-randomized clinical trial which was regarded as two independent studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, when treatment was divided into 2 periods (2007–2010 and 2011–2013) to reflect the routine use of MDCT or 3D TEE for annular sizing at our institutions from 2011 onward, we detected a 50% reduction in the proportion with PPM during the recent period. Although our data are only hypothesis generating, this may reflect larger‐size prosthesis and better prosthesis selection guided by 3D modalities in the latter period. In our study, no case of PPM occurred with the largest prostheses (Edwards SAPIEN 29 mm or Medtronic CoreValve 29–31 mm), which were typically not available during most studies reporting PPM post‐TAVR.…”
Section: Discussionmentioning
confidence: 85%
“…[20] da Silva et al . [21] showed that patients who had 3D TEE measurements of the aortic annulus had a significantly ( P = 0.03) lower incidence of severe PPM after transcatheter AV implantation (TAVI) when compared to those who had annulus measured using 2D TTE (0% with 3D TEE vs. 20% with 2D TTE). While computerized tomography is the most accurate methodology for measuring aortic annulus preoperatively before TAVI, 3D TEE is the most practical method in the operating room for measurement of annular diameter during surgical AVR (SAVR).…”
Section: Echocardiographic Measurements Relevant To Ppmmentioning
confidence: 99%